A prospective, randomized, masked, placebo‐controlled crossover study for the effect of 10 mg omeprazole capsules on gastric pH in healthy dogs. (15th February 2021) - Gaier, Ann; Price, Josh; Grubb, Louise; Fitzgerald, Stuart; Tolbert, M. Katherine
Abstract: Background: Enteric‐coated omeprazole capsules are commonly used as a gastric acid suppressant in dogs. However, the efficacy of this formulation has not been evaluated for clinical use in dogs. Hypothesis/Objectives: To evaluate the efficacy of a 10 mg PO omeprazole capsule (TriviumVet) undergoing FDA approval to increase gastric pH in dogs. We hypothesized that encapsulated omeprazole would significantly increase the gastric pH compared to placebo and reach pH goals extrapolated from people for the treatment of esophagitis and duodenal ulceration. Animals: Six healthy research dogs. Methods: Randomized, blinded, 2‐way crossover study. Dogs were PO administered omeprazole at 0.5 to 1.0 mg/kg or placebo (empty gelatin capsules) twice‐daily for 5 days. The intragastric pH was recorded on days 2 to 5 of treatment. Mean pH and the mean percentage time (MPT) intragastric pH was ≥3 or ≥4 were compared between and within treatment groups. Results: Dogs treated with omeprazole had a significantly higher MPT ± SD intragastric pH ≥3 (91.2% ± 11.0%), ≥4 (86.9% ± 13.7%) and mean ± SD pH (5.4 ± 0.8) than dogs treated with placebo (19.7% ± 15.5%, 28.3 ± 20.7, and 2.4 ± 1.0, respectively) ( P < .001 for all). Conclusions and Clinical Importance: The 10 mg enteric‐coated omeprazole capsule PO administered evaluated in this study is an effective gastric acid suppressant in healthy dogs.